Gaia’s Crown: a deep space mirage seen from DSCOVR/EPIC during lunar transit - Blank, Karin; Herman, Jay; Dangelo, Sarah; Marshak, Alexander; Tennenbaum, Andrew (Frontiers in Remote Sensing, 2026)
The Earth Polychromatic Imaging Camera (EPIC), onboard the Deep Space Climate Observatory (DSCOVR) spacecraft, located at the Earth-Sun Lagrange 1 point, has captured a unique optical effect during lunar occultation named “Gaia’s Crown.” In EPIC images, the phenomenon appears as a small “flange” at the Earth–Moon contact when the Moon is roughly half below Earth’s limb; it is present in the visible and near-infrared channels but absent in the ultraviolet. Using atmospheric data and 3D, voxel-based ray tracing models, this effect was identified as a combination of atmospheric distortion and a complex mirage caused by variations in the Earth’s atmosphere. Additionally, it is shown that while satellites closer to the Earth can see a similar phenomenon, Gaia’s Crown presents unique distortion effects that demonstrate how EPIC’s vantage point at 1.5 million kilometers from Earth provides a different perspective on atmospheric optics.